Correlation between daily physical activity and intestinal microbiota in perimenopausal women - Yanqiu Zheng; Junyu Ke; JinBin Song; Xuyu Li; Rongman Kuang; Haiyan Wang; Shuang Li; Yanwu Li (Sports Medicine and Health Science)
This study aimed to examine the correlation between daily physical activity levels and gut microbiota during the perimenopausal period. To explore the physiopathological traits of perimenopause women, and provide a theoretical basis for the development of menopause exercise intervention program. In this study, daily physical activity was assessed using the ActiGraph wGT3X-BT wearable sensor, and 16S rRNA sequencing was employed to analyze gut microbiota diversity and composition. Comparative analysis was conducted to evaluate the association between physical activity and specific phyla and genera in the gut microbiota, comparing perimenopausal women to youth women. The results showed perimenopausal women exhibited significantly lower levels of daily physical activity, including Kcals, metabolic equivalents (METs), and moderate-to-vigorous physical activity (MVPA), compared to youth women. The composition of the gut microbiota was markedly different between the two groups. Specifically, the abundance of Acidobacteria, Chloroflexi, Nitrospirae, and Gemmatimonadetes were lower at the phylum level (p < 0.01). Collinsella, Ruminococcus gnavus, Rothia, Haemophilus, Sphingomonas, Lactobacillales, and Lactococcus were lower at the genus level, while Phascolarctobacterium, Paraprevotella, Acinetobacter, Flavonifractor, and Intestinimonas exhibited a significant increase (p < 0.05, p < 0.01). Furthermore, a positive correlation was observed between Chloroflexi or Sphingomonas and physical activity (kcals, METs, and MVPA), while a negative correlation was found between Intestinimonas and physical activity (METs: p < 0.01, and MVPA: p < 0.05). Doubtlessly, the perimenopausal period is associated with lower levels of physical activity and distinct changes in gut microbiota. Sphingomonas may serve as a sensitive bacterium closely linked to physical activity.